Reduction of common mode voltage for grid-connected multilevel inverters using fuzzy logic controller - Quang-Tho Tran; Vinh-Quan Nguyen (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Cascaded multilevel three-phase inverters are increasing in industries of electric drives and renewable energy because of their large capacity and suffering from high voltage shock. However, the high magnitude of common mode voltage is one of the drawbacks. Thus, the techniques of modulation and control in these multilevel inverters significantly affect the power quality of the output voltage of inverters. This paper presents a technique using fuzzy logic technique for grid-connected cascaded multilevel 3-phase inverters. This technique has completely removed the current controllers and the conventional modulation using carriers. It also helps reduce the magnitude of common mode voltage and increase the dynamic response. Moreover, the ability to reduce harmonics and switching count also helps decrease the switching loss of inverter. The simulation results on a grid-connected cascaded 5-level 3-phase inverter have validated the effectiveness of the presented technique compared with that of the conventional method using phase opposition disposition (POD) and PI current controllers.